Tipologi Multiakad Dalam Fatwa Ekonomi Digital Dewan Syariah Nasional Majelis Ulama Indonesia - Ulum, Kefi Miftachul; Fuad, Ahmad Zaky; Khairunnisa, Maulida; Mawadah, Atina Rahmah; Pratama, M. Rafirsa Agung (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2024)
This study aims to analyze the urgency of the typology of a contract which is commonly used by the community for fulfilling daily digital-based needs. Some contend that merging contracts breaches Sharia principles, while others believe it is permitted with limitations. Aside from the debate in the current digital-based era, muamalah transaction activities have evolved and grown towards a modern direction that is carried out online; however, due to low literacy and interest in reading, the general public is unaware that this involves multiple contracts. The fatwa given by the DSN MUI institution does not cover the complete scope of so many contracts. These concerns will be analyzed employing a normative legal research methodology that adopts a conceptual approach. The DSN MUI Fatwa and Community practices represent the study's primary data, while the literature on contract typology is used for secondary data. The research discovered that people practice muamalah or contract employing multiple agreements without realizing it. Additionally, the DSN MUI Fatwa does not cover it all in one integrated fatwa formulation. The findings of the present research can also be used to cluster muamalah or contract practices with multi-agreement typologies, which will facilitate the general public's understanding of the participating behaviors.